How robust is the moderating effect of extremist beliefs on the relationship between self-control and violent extremism? - Pauwels, Lieven (Crime & delinquency, 2017)
The present research note studies the interaction between the ability to exercise self-control and extremist moral beliefs with regard to the explanation of violent extremism. Although some evidence exists for the interaction between moral beliefs and self-control in the explanation of adolescent offending, no previous study has studied this interaction effect in a survey of young adults and with regard to politically or religiously motivated violence. This study therefore extends the existing literature by testing a key proposition of Situational Action Theory. We use a large-scale web survey of young adults in Belgium. The results support the hypothesis that the effect of the ability to exercise self-control is conditional upon one’s extremist beliefs. The results are stable across extremism-specific measures of extremist beliefs.